Developing and Implementing Technology of Rosé Wine Production from the Grape Variety “Charentsi” - Gabrielyan, A. H.; Simonyan, N. R.; Gasparyan, A. S. (ՀԱԱՀ հիմնադրամ)
The research results indicate that the demand for high quality and unique wines is eventually increasing. The goal of the research was to develop and implement technologies of rosé wine production from little studied teinturier grape variety “Charentsi”, for getting high-quality product according to the international standards. During the study, rosé wines were produced from the abovementioned grape varieties by applying different techniques. Besides, physicochemical and organoleptic evaluation for all wine samples were carried out.
Keywords: Food Science and Technology